A década de Extremo(z): crescimento populacional e transformações urbanas no município da RMN - Morais, Erociano Vitor Freitas (2025)
Starting in 1950s, Brazil underwent a rapid process of urbanization, characterized by inequality and a lack of infrastructure. As cities grew, peripheries areas expanded, and major urban centers began to exert increasing influence over their surroundings, giving rise to the metropolitan phenomenon. In the 1970s, Complementary Laws Nº. 14/1973 and Nº. 20/1974 established Brazil’s first nine metropolitan regions (MRs), centered on the cities of São Paulo (SP), Rio de Janeiro (RJ), and Belo Horizonte (MG) in the Southeast; Recife (PE), Fortaleza (CE), and Salvador (BA) in the Northeast; Curitiba (PR) and Porto Alegre (RS) in the South Region; and Belém (PA) in the North. With the country’s re-democratization and the promulgation of the 1988 Federal Constitution, the creation of MRs became the responsibility of individual states. From the 1990s onward, several new metropolitan regions were instituted, encouraged by the possibility of accessing credit lines and specific financing programs for those territories. The Metropolitan Region of Natal (MRN) emerged in this context, legally instituted in 1997, initially encompassing the municipalities adjacent to the city of Natal, which serves as the metropolitan hub. Over time, more municipalities were included, leading to a distinction between the institutional MRN (legally defined) and the functional MRN (defined by regional flows and dynamics). During this process, Natal expanded, extending its influence into neighboring municipalities, including Extremoz. This study analyzes the metropolitan phenomenon in the MRN, focusing on the significant population growth of Extremoz/RN, which recorded the third-largest relative population increase in Brazil between 2010 and 2022. In this context, the study aims to examine the factors driving Extremoz’s populacion growth during the period between the 2010 and 2022 Censuses, consideting Natal’s spillover effect toward the northern metropolitan axis, the municipality's urban dynamics, and its economic evolution. The research methodology includes a review of literature on the urbanization process in Brazil and worldwide, as well as the emergence of the metropolitan regions. Additionally, documentary and historical research on Extremoz was carried out, alongside photographic surveys in the municipality, spatial analyses using satellite imagery, and the organization of various databases. Notable among these are data from agencies such as IBGE, SNH, MTE, and the Municipal Secretariats of Extremoz. The main findings identcate that Extremozs growtg stemmed from several interrelated factors: the spillover of population from Natal, driven by the expansion of the North Administrative Region and the construction of new road accesses, such as the Newton Navarro Bridge and Conselheiro Tristão Street; the expansion of the real estate market, including the development of multiple subdivisions and housing projects, resulting in two urban expansion fronts in the municipality; and economic growth, particularly the increase in formal employment and the emergence of new business establishments, fostering the creation of a self-sustaining local supply market.